Determinants of Nutritional Status among Malnourished Children in Agricultural Areas - Susanto, Tantut; Herminiati, Ainia; Rohmawati, Ninna; Yunanto, Rismawan Adi; Rahmawati, Ira; Bachtiar, Syahroni; Merina, Nuning Dwi; Zolkefli, Yusrita binti (Jurnal Keperawatan Soedirman, 2024)
Stunting in children is a major global issue, especially in rural agricultural areas of Indonesia. Despite ongoing efforts to eliminate stunting, its prevalence remains high, adversely affecting children's cognitive and physical development. This study aimed to determine the factors influencing the nutritional status of stunted children in Indonesia’s agricultural districts. A cross-sectional analytical study was conducted in Jember District, Indonesia, involving 236 malnourished children aged 0 to 59 months. Using stratified random sampling, structured questionnaires were utilized to collect data on family functioning, child feeding attitudes, and practices. The results are Family Function (B=0.038; 95% CI= 0,535 – 1,658, p value= 0.047); Child Feeding Attitude (B=0.030; 95% CI= 0,882 – 1,681, p value= 0.023); and Child Feeding Practice (B=0.120; 95% CI= 0,686 – 1,971, p value= 0.000). There were significant correlations between family function (p value= 0.047), child-feeding attitudes (p value= 0.023), and child-feeding practice (p value= 0.000) with children's nutritional status. This study highlighted a significant relationship among family function, child-feeding attitude, and practices concerning the nutritional status of children experiencing stunting. It emphasizes the importance of improving family function and supporting healthy child-feeding practices. Targeted interventions based on local cultural understanding are critical for effectively reducing stunting.